The Annulment of Homologation in the Case of PKPU Application of Intidana Savings and Loan Cooperative in Review of Law Number 37 of 2004 - A.A.P*, Karina Widyadhari; Gultom, Elisatris; Afriana, Anita (Universitas Syiah Kuala, 2023)
The purpose of this research is to find out the annulment of homologation in the case of a PKPU application for KSP Intidana in terms of Law No. 37 of 2004. This research method is normative juridical which is guided by primary legal materials and secondary legal materials contained in a legislation. The results of the research show that first, the action of not accepting the annulment of homologation on the basis that the application submitted was premature is not in accordance with the provisions of the KPKPU Law because the concept of negligence as a reason for homologation annulment in the KPKPU Law is interpreted as an action where the debtor really does not fulfill the clauses agreed upon in the composition agreement, not waiting until the payment deadline expires. Secondly, the judge's action in not accepting the homologation annulment request submitted by KSP Intidana's creditors was inappropriate because it did not fulfil one of the principles of the decision in which the judge's decision must contain a clear basis.